Determinants of Hospital Length of Stay among Patients with Pneumonia Admitted to a Large Canadian Hospital from 1991 to 2001 - Margaret J McGregor; J Mark FitzGerald; Robert J Reid; Adrian R Levy; Michael Schulzer; David Jung; Horacio E Groshaus; Michelle B Cox (Canadian Respiratory Journal)
BACKGROUND: Pneumonia is a common reason for hospital admission, and the cost of treatment is primarily determined by length of stay (LOS).